Investigation the sustainable additive influence, obtained from milk protein, in the chemical and physical properties of Portland cement. (15th October 2019) - Dias de Souza, Clarissa; Gonçalves Dias de Souza, Nelson Luis; Gomes Barbosa, Maria Teresa; Stephani, Rodrigo; Cappa de Oliveira, Luiz Fernando
Abstract: For the construction industry, the term technological innovation for applicable materials equalizes costs, improves and rationalizes the final product quality. In this context, the researches of organic and inorganic additives are standing out in the production of cement compounds, which satisfy the technical and environmental requirements for the area. In this work, it has been analyzed the feasibility of the use of a biodegradable polymer, in the case we have used the complexes of whey protein with κ-casein, the κ-casein is a phosphoprotein found in milk, obtained from milk which was unfit for human consumption; the main idea is to use it as a collaborative agent in the physicochemical properties of the binder. In this sense, different amounts of solutions of the complexes of whey protein with κ-casein were added to Portland cement samples and the influence of these solutions on the hydration process of the binder were analyzed by Raman spectroscopy. As a result, it was observed that the use of the solutions of the complexes of whey protein with κ-casein favors the cement hydration process, which can retard the setting of the binder; such result is desirable, as it provides a greater flexibility to the setting time, increasing the workability time of the binder. Highlights: Casein obtained from milk unfit for human consumption favors the cement hydration process. Reducing the water/cement factor. The favorable situations for self-healing in cementitious materials are strengthened. The sustainable development concept is strengthened for building industry.